Increased PENINGKATAN COLLABORATION SKILLS DALAM KEGIATAN PRAKTIKUM FISIKA DASAR MAHASISWA PROGRAM STUDI TEKNOLOGI PANGAN UNU PURWOKERTO - Asti Dewi Nurhayati; Laksmi Putri Ayuningtyas; Hikmah Yuliasari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2021)
The purpose of this research was to observe the student’s collaboration of food technology department in 2019 through basic physics practicum. The research method used classroom action research which was divided into four parts, that is planning, action, observation, and reflection. This research was done into four groups and accompanied by each observer. They had to take responsibility to observe the collaboration skill of each student in the group. The results of this research showed that the collaboration skill increased in every part. Group one of the first part showed a result of 45% with moderate success criteria, it increased in the second part to 51.11% (moderate), it increased in the third part to 76.67% (high), and it increased in the fourth part to 92.78% with very high success criteria. So it happened in group two, group three, and group four. Group two of the first part showed a result of 42.22% (moderate), in the second part to 51.117% (moderate), in the third part to 71.67% (high) and in the fourth part to 90% (very high). Group three of the first part showed a result of 46% (moderate), in the second part to 52.67 (moderate), in the third part to 79.33% (high), and in the fourth part to 92.67% (very high). Group four of the first part showed a result of 39.33% (low), in the second part to 56% (moderate), in the third part to 82.67% (very high), in the fourth to 92% (very high).